“There’s Just No Real Way to Win”: Disabled Archivists and Professionalism’s Paradox - Brilmyer, Gracen; Denison, Veronica; Sadler, Jill; Brar, Tara (Archivaria)

(untitled) (Association of Canadian Archivists, 2024)
Centring around first person accounts, this article shows how some disabled archivists have experienced many different ableist expectations and assumptions in their work: through requirements in job descriptions, performance, and productivity and attitudes around comportment, accommodations, and disability. Drawing on a wide array of literature on disability, affect, and the archival profession while using data collected through interviews with disabled archivists, this article highlights some affective dimensions of archival labour. Interviewees’ past experiences led to an acute awareness of how they might or might not be perceived as “professional.” And managing this awareness and their concerns led to a variety of strategies: participants described overperforming, denying their own needs, and “pushing through” as well as expending significant amounts of time, energy, and work in anticipating, navigating, and managing others’ feelings and ableist attitudes. Together, these findings outline some of the ways disabled people experience the archival profession, perform labour that might be less legible and under-recognized, and feel about their place in the profession. Moreover, such labour illustrates a double bind for disabled archivists – what we might call a paradox of archival ableism. As they navigate others’ assumptions about disability – discriminatory opinions about capabilities, harmful behaviour, and ableist expectations – they simultaneously have to overperform, advocate for their own worthiness for accommodations, and balance the ways these efforts might counteract, contradict, or work against each other. In other words, the paradox of archival ableism is how ableism produces a double bind of having to prove that one is both capable of work and also deserving of the very accommodations needed to do the work and how these efforts often work against each other.